ANALYZING HOW STORE IMAGE DIMENSION AFFECTS CONSUMER SPENDING. (A CASE OF GIANT EKSTRA AND TRANSMART CARREFOUR IN MANADO) - Siahu, Laurensia Pelesia; Saerang, David P. E.; Tasik, Hizkia H.D (Universitas Sam Ratulangi, 2017)
Abstract: Manado city is experiencing a rapid economic development, it can be seen from the minimum wage which is the third largest in Indonesia and the largest in Sulawesi Island. This condition attracts some new retailers to do market expansion in Manado City, two of the latest entrance are Giant Ekstra and Transmart Carrefour. Their brand awareness is not as good as other retailers, meaning people in Manado are still evaluating whether these stores suit their shopping preference or not.Â Previous research found that store image has a positive effect on store loyalty through store satisfaction which may lead to moreÂ spending of money in the stores. The result of this research may later be used as a strategy for both stores. A casual type of research is adapted which uses primary data obtained through questionnaires and uses Ordinal Regression Analysis. The population is the people in Manado who already have shopping experience in both stores with 200 respondents as the sample size. The results turns out that Store Image does not significantly affects Consumer Spending. For recommendations, the retailers in Manado better give more effort in upgrading their pricing system and product quality control rather than upgrading their store image.Keywords: Store Image, Consumer Spending, Consumer Behavior, Retail